2021
DOI: 10.1002/fsn3.2552
|View full text |Cite
|
Sign up to set email alerts
|

Comparative metabolomics reveals differences in primary and secondary metabolites between “Shixia” and “Chuliang” longan (Dimocarpus longan Lour.) pulp

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 45 publications
0
10
0
Order By: Relevance
“…In our study, the contents of organic acids, such as citramalic acid and succinic acid, accumulated in cultivated loquats, suggesting that cultivated loquats have stronger taste. Previous studies have indicated that the components and content of organic acids contribute to the taste of longan fruits [ 47 ]. Besides sugars, organic acids have an impact on the good taste of strawberry fruits [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our study, the contents of organic acids, such as citramalic acid and succinic acid, accumulated in cultivated loquats, suggesting that cultivated loquats have stronger taste. Previous studies have indicated that the components and content of organic acids contribute to the taste of longan fruits [ 47 ]. Besides sugars, organic acids have an impact on the good taste of strawberry fruits [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Besides sugars, organic acids have an impact on the good taste of strawberry fruits [ 46 ]. Furthermore, flavonoids are the key chemicals that contribute to the medicinal and nutritional characteristics of fruits [ 47 ]. In our work, most of the flavonoid biosynthesis-related genes were significantly upregulated in wild loquats ( Supplementary Data Table S14 ).…”
Section: Discussionmentioning
confidence: 99%
“…The total phenolic content (TPC) and total flavonoid content (TFC) of longan pericarp and aril were measured according to the previously reported methods [ 2 ]. The ethanolic extract used for determination of TPC and TFC contents was prepared by homogenizing 0.1 g frozen pericarp or 0.3 g frozen aril, which was extracted with 1 mL 80% ethanol using a vigorously vortex and ultrasonication (KQ 5200E, Kunshan Ultrasonic Instrument Co., Ltd., Kunshan, China) for 60 min.…”
Section: Methodsmentioning
confidence: 99%
“…After a centrifugation at 12,000× g for 10 min, the supernatant of each sample was used to determine TPC and TFC. The TFC was measured at 510 nm according to the method reported by Lai et al [ 2 ] using a standard curve of rutin and the TPC was assayed at 760 nm by the Folin–Ciocalteu method using gallic acid as the standard [ 2 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation